KPC-producing Klebsiella pneumoniae in Switzerland from 2024 to 2025: comparative genomics and cefiderocol resistance mechanisms analyses - Jacqueline Findlay; Patrice Nordmann; R Lienhard; L Vonallmen; C Schilt; A Scherler; K Lucke; M Jutzi; M Reichmuth; U Schibli; C Fricker; S Pranghofer; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

In vitro activity of β-lactamase inhibitors avibactam, relebactam and vaborbactam in combination with aztreonam against metallo-β-lactamase producing Escherichia coli clinical isolates - Clément Viguier; Samanta Freire; Maxime Bouvier; Christophe Le Terrier; Laurent Poirel; A. Westers; M. Imperiali; L. Pozzi; D. Balzari; G. Vaninetti; C. Cirillo; V. Gaia; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

HoWDe: A validated algorithm for Home and Work location Detection - Sílvia de Sojo; Lorenzo Lucchini; Ollin D. Langle-Chimal; Samuel P. Fraiberger; Laura Alessandretti (Computers, Environment and Urban Systems, 2026)

Molecular analysis of metallo-beta-lactamase-producing Pseudomonas aeruginosa in Switzerland 2022–2023 - Jacqueline Findlay; Otavio Hallal Ferreira Raro; Laurent Poirel; Patrice Nordmann; R. Lienhard; L. Vonallmen; C. Schilt; A. Scherler; K. Lucke; M. Jutzi; M. Reichmuth; U. Schibli; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Objectives The occurrence of metallo-beta-lactamase-producing Pseudomonas aeruginosa (MBL-PA) isolates is increasing globally, including in Switzerland. The aim of this study was to characterise, phenotypically and genotypically, the MBL-PA isolates submitted to the Swiss National Reference Center for Emerging Antibiotic Resistance (NARA) reference laboratory over a 12-month period from July 2022 to July 2023. Methods Thirty-nine non-duplicate MBL-PA Isolates were submitted to NARA over the study period from across Switzerland. Susceptibility was determined by broth microdilution according to EUCAST methodology. Whole-genome sequencing was performed on 34 isolates. Sequence types (STs) and resistance genes were ascertained using the Centre for Genomic Epidemiology platform. MBL genes, bla NDM-1 , bla IMP-1 , and bla VIM-2 , were cloned into vector pUCP24 and transformed into P. aeruginosa PA14. Results The most prevalent MBL types identified in this study were VIM (21/39; 53.8%) followed by NDM (11/39; 28.2%), IMP (6/39; 15.4%), and a single isolate produced both VIM and NDM enzymes. WGS identified 13 different STs types among the 39 isolates. They all exhibited resistance to cephalosporins, carbapenems, and the beta-lactam-beta-lactamase inhibitor combinations, ceftolozane-tazobactam, ceftazidime-avibactam, imipenem-relebactam, and meropenem-vaborbactam, and 8 isolates were cefiderocol (FDC) resistant. Recombinant P. aeruginosa strains producing bla NDM-1 , bla IMP-1 , and bla VIM-2 exhibited FDC MICs of 16, 8, and 1 mg/L, respectively. Conclusions This study showed that the MBL-PA in Switzerland could be attributed to the wide dissemination of high-risk clones that accounted for most isolates in this study. Although FDC resistance was only found in 8 isolates, MBL carriage was shown to be a major contributor to this phenotype.

World Trade Center Site Exposure Duration Is Associated with Hippocampal and Cerebral White Matter Neuroinflammation - Chuan Huang; Minos Kritikos; Mario Serrano Sosa; Thomas Hagan; Alan Domkan; Jaymie Meliker; Alison C. Pellecchia; Stephanie Santiago-Michels; Melissa A. Carr; Roman Kotov; Megan Horton; Sam Gandy; et al. (Molecular Neurobiology, 2023)
Responders to the World Trade Center (WTC) attacks on 9/11/2001 inhaled toxic dust and experienced severe trauma for a prolonged period. Studies report that WTC site exposure duration is associated with peripheral inflammation and risk for developing early-onset dementia (EOD). Free Water Fraction (FWF) can serve as a biomarker for neuroinflammation by measuring in vivo movement of free water across neurons. The present case-controlled study aimed to examine associations between WTC site exposure duration as well as EOD status with increased hippocampal and cerebral neuroinflammation. Ninety-nine WTC responders (mean age of 56) were recruited between 2017 and 2019 ( N = 48 with EOD and 51 cognitively unimpaired). Participants were matched on age, sex, occupation, race, education, and post-traumatic stress disorder (PTSD) status. Participants underwent neuroimaging using diffusion tensor imaging protocols for FWF extraction. Region of interest (ROI) analysis and correlational tractography explored topographical distributions of FWF associations. Apolipoprotein-e4 allele ( APOE ε4) status was available for most responders ( N = 91). Hippocampal FWF was significantly associated with WTC site exposure duration ( r = 0.30, p = 0.003), as was cerebral white matter FWF ( r = 0.20, p = 0.044). ROI analysis and correlational tractography identified regions within the limbic, frontal, and temporal lobes. Hippocampal FWF and its association with WTC exposure duration were highest when the APOE ε4 allele was present ( r = 0.48, p = 0.039). Our findings demonstrate that prolonged WTC site exposure is associated with increased hippocampal and cerebral white matter neuroinflammation in WTC responders, possibly exacerbated by possession of the APOE ε4 allele.

Multinational evaluation of the BioFire® FilmArray® Pneumonia plus Panel as compared to standard of care testing - Christine C. Ginocchio; Carolina Garcia-Mondragon; Barbara Mauerhofer; Cory Rindlisbacher; L. Forcelledo; J. Fernández; R. Lienhard; H. Kerschner; G. M. Rossolini; L. Armand-Lefèvre; C. d’Humières; E. Cambau; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
This study compared standard of care testing (SOC) to BioFire® FilmArray® Pneumonia plus Panel (PN plus ). PN plus detects 15 bacteria with semiquantitative log bin values, 7 antibiotic resistance markers, three atypical bacteria (AB), and eight viral classes directly from bronchoalveolar lavage-like specimens (BLS) and sputum-like specimens (SLS). Fifty-two laboratories from 13 European countries and Israel tested 1234 BLS and 1242 SLS with PN plus and SOC. Detection rates and number of pathogens/samples were compared for PN plus pathogens. PN plus bin values and SOC quantities were compared. Three thousand two hundred sixty-two bacteria in PN plus were detected by PN plus and/or SOC. SOC detected 57.1% compared to 95.8% for PN plus ( p ≤ 0.0001). PN plus semiquantitative bin values were less than SOC, equal to SOC, or greater than SOC in 5.1%, 25.4%, and 69.6% of results, respectively. PN plus bin values were on average ≥ 1 log than SOC values (58.5% 1–2 logs; 11.0% 3–4 logs). PN plus identified 98.2% of MRSA and SOC 55.6%. SOC detected 73/103 AB (70.9%) and 134/631 viruses (21.2%). PN plus detected 93/103 AB (90.3%) and 618/631 viruses (97.9%) ( p ≤ 0.0001). PN plus and SOC mean number of pathogens/samples were 1.99 and 1.44, respectively. All gram-negative resistance markers were detected. PN plus and SOC results were fully or partially concordant for 49.1% and 26.4% of specimens, respectively. PN plus was highly sensitive and detected more potential pneumonia pathogens than SOC. Semiquantification may assist in understanding pathogen significance. As PN plus generates results in approximately 1 h, PN plus has potential to direct antimicrobial therapy in near real time and improve antimicrobial stewardship and patient outcomes.

Multi-parametric cardiorespiratory analysis in late-preterm, early-term, and full-term infants at birth - Maristella Lucchini; Nina Burtchen; William P. Fifer; Maria G. Signorini (Medical & Biological Engineering & Computing, 2019)

Metal partitioning in plant–substrate–water compartments under EDDS-assisted phytoextraction of pyrite waste with Brassica carinata A. Braun - T. Vamerali; M. Bandiera; P. Lucchini; G. Mosca (Environmental Science and Pollution Research, 2015)

Increased bioavailability of metals in two contrasting agricultural soils treated with waste wood-derived biochar and ash - P. Lucchini; R.S. Quilliam; T.H. DeLuca; T. Vamerali; D.L. Jones (Environmental Science and Pollution Research, 2014)